Efeitos da ação conjunta do fator-1 de crescimento semelhante à insulina e da quimiocina cc-ligante 2 sobre a migração de células endoteliais - Viana, Iana Mayane Mendes Nicácio (2013)
The influence of insulin-like growth factor-1 (IGF-1) and CC-chemokine ligand 2 (CCL2) on vascular function and angiogenesis have been the subject of several studies which demonstrate their proangiogenic effects. Knowing that endothelial cell migration can be stimulated by angiogenic factors and seeking to understand the interaction of these factors in endothelial migration process, the present study aimed to investigate in vitro effects of IGF-1 and/or CCL2 on endothelial cells. We applied the murine thymic endothelial cell line (tEnd.1) treated with IGF-1 (100 ng/mL), CCL2 (10 ng/mL) or IGF-1/CCL2 for 24 hours. Flow cytometry analysis showed that treatment with IGF-1 and/or CCL2 did not change IGF-1 receptor expression (IGF-1R) on tEnd.1 cells as compared to untreated cultures. However, CCL2-treatment increased expression of its receptor, CCR2, on tEnd.1 cells. Immunofluorescence analysis of tEnd.1 cells revealed that IGF-1 and/or CCL2 increased fibronectin (FN) deposition, but they did not alter FN receptors, alpha chain of α5β1/VLA5 integrin (CD49e) and CD44 transmembrane proteoglycan as analyzed by flow cytometry. By Immunofluorescence was also revealed alterations on F-actin cytoskeleton in these cells for all treatments onto fibronectin coating. In the adhesion assay, tEnd.1 cells treated with IGF-1 and/or CCL2 increased adhesion to fibronectin coated-surfaces as well as cell migration in transwell chambers assessed on fibronectin coated-surface. Morphological analysis demonstrated that only tEnd.1 cells treated with IGF-1/CCL2 for 12 and 24 hours presented intracellular lumens. Finally, luminal area and tEnd.1 tube formation were increased by IGF-1 and/or CCL2 treatment on fibronectin. These data suggest that IGF-1 and/or CCL2 stimulate in vitro cytoskeleton reorganization, adhesion, migration and endothelial cell tube formation by tEnd.1 cell line on fibronectin matrix protein, so they can contribute for angiogenesis process.